Ketoconazole بعض التغايرات الفسلجيه والنسيجيه في ذكور الجرذان المختبريه المعرضه لجرع مختلفه من المضاد الفطري - عباس, حسن (University of Thi-Qar Journal of Science, 2010)
This study was performance to investigate the effect of over doses(high dose and long term) of antifungal ketoconazole on body weight, liver weight, Biochemical parameters (ALP, AST and ALT enzymes, as well as total protein and cholesterol concentrations), andhistological study of liver . For this purpose twenty adult male rats were divided randomly into equal four groups as below: Animals of control were treated with drinking water, first group (T1) treated with drinking water and 1.5mg/kg of body weight of ketoconazole, second group (T2) treated with drinking water and 3mg/kg of body weight of ketoconazole, third group(T3) treated with drinking water and 6mg/kg of body weight of ketoconazole, At the end of treatment, animalswere weighted, and anesthetized, blood draw was done to biochemical tests, then animals were sacrificed and dissected, after that liver, were eradication to weighted and prepared histological slide. The results revealed that the different concentrations of ketoconazole led to significantdecrease (P<0.05) in body weight in T2 and T3 comparison with control group, and significant decrease in total protein and cholesterol concentrations in T3 comparison with control group. Where as significant increase (P<0.05) in liver weight in T3 and significant increase (P<0.05) in transamines enzymes (AST, ALT), Alkaline phosphate enzyme (ALP), in T1, T2 and T3 comparison with control group.